Strategi Pengembangan Kompetensi Calon Guru SD terhadap Penerapan Kurikulum Merdeka - Novi Andri Nurcahyono (LPPM Universitas Terbuka, 2023)
The Merdeka Curriculum has been implemented, but various kinds of obstacles are still found by schools and teachers in its implementation. For this reason, it is necessary to prepare prospective teachers for the implementation of the Merdeka Curriculum by looking for the necessary competency development strategies. This study aims to analyze the competencies needed by prospective teachers in implementing the Merdeka Curriculum and its development strategy. This research is a library research study on articles related to the characteristics of the Merdeka Curriculum and the difficulties in its application. As a result, the competencies that need to be developed are pedagogic, professional, personal and social competencies that have been adapted to the characteristics of the Merdeka curriculum. The competencies developed are related to the preparation of simpler learning modules, the preparation of learning objectives that are tailored to the characteristics of each student, the use of learning models and media that can increase student creativity, the use of technology in the implementation and evaluation of learning. So the strategy that can be used to achieve these competencies is to integrate the competency development of prospective teachers in related subjects. In addition, it is necessary to hold socialization and technical guidance about the Merdeka Curriculum, so that prospective teachers can achieve four competencies in implementing the Merdeka Curriculum learning.